2005
DOI: 10.1007/s00268-005-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Minimal Access Surgery for Cancer Associated with Immunologic Benefits?

Abstract: Minimal-access surgical techniques have been shown to be beneficial to patients in terms of shorter convalescence, reduced pain, and improved cosmesis. Although systemic immune function is better preserved following laparoscopic procedures when compared with their respective open approaches, CO2 pneumoperitoneum may significantly affect local (i.e., infra-abdominal) cellular immunity by reducing regional macrophage function. Results to date are conflicting with regard to the impact of closed and open methods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 97 publications
(104 reference statements)
0
59
1
Order By: Relevance
“…After minor surgical procedures, the vast majority of studies have reported lower postoperative IL-6 and CRP when compared to open procedures [24]. Results from studies comparing SIR and acute phase response in laparoscopy vs. open after major surgery are ambiguous [3,24,25]. A possible reason for this is that the difference in tissue trauma between laparoscopic and open surgery may not be as pronounced after major surgical procedures.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…After minor surgical procedures, the vast majority of studies have reported lower postoperative IL-6 and CRP when compared to open procedures [24]. Results from studies comparing SIR and acute phase response in laparoscopy vs. open after major surgery are ambiguous [3,24,25]. A possible reason for this is that the difference in tissue trauma between laparoscopic and open surgery may not be as pronounced after major surgical procedures.…”
Section: Discussionmentioning
confidence: 87%
“…A key function of IL-6 is the mediation of acute phase response, reflected by the rapid rise in IL-6 and CRP levels in the early postoperative period. After minor surgical procedures, the vast majority of studies have reported lower postoperative IL-6 and CRP when compared to open procedures [24]. Results from studies comparing SIR and acute phase response in laparoscopy vs. open after major surgery are ambiguous [3,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The thesis is well documented in multiple studies comparing postoperative increase of acute phase response factors like CRP, IL-1, IL-6, TNF-= after conventional and laparoscopic colon resection (14,27). Laparoscopic surgery is associated with minimal manipulations of the tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Minimizing the operative trauma leads to less immune supression, less impairment of plasma proteins and less stimulation of neoangiogenesis (6,7,9,14,19,20,21,26,27,28). These phenomenons, dependently of extensiveness of surgical procedure may contribute to unintended tumor growth and survival of cancer cells in the operative field, blood stream and distant organs.…”
Section: R E V I E W P a P E R Smentioning
confidence: 99%
See 1 more Smart Citation